Intermetallic cobalt–gallium targets for production of germanium radioisotopes. (September 2022) - Kutyreff, C.J.; Barnhart, T.E.; Lo, Y.H.; Happel, S.; Nickles, R.J.; Ellison, P.A.; Aluicio-Sarduy, E.; Engle, J.W.
Abstract: Increasing interest in targeted radionuclide therapy motivates the development of new radionuclides. The unique emission spectrum from 71 Ge make it an ideal candidate for probing microdosimetric effects of low energy electrons absent confounding photon dose. This work reports a novel intermetallic target of Co and Ga for accelerator production of no-carrier-added 69/71 Ge and a new method to isolate the Ge in high yields and purities. Highlights: Novel Co + Ga intermetallic targets enable cyclotron production of 69/71 Ge. Branched DGA extraction chromatography isolates 69/71 Ge in high purity. First report of 71 Ge yield in CoGa targets using low-energy X-ray spectrometry.